KOMPETENSI GURU PAI DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA - Siti Hawa (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
This study entitled "PAI teacher competence and its influence on student achievement". The purpose of this study was to determine the role of school principals in empowering the competence of PAI teachers, to find out the effect of Islamic education teacher competence on student achievement and the factors that influence student learning outcomes. The research results obtained show that the role of school principals in empowering PAI teachers is as educators, managers, administrators, supervisors, leaders (leaders) and as innovators. The competencies possessed by PAI teachers are known to have a positive influence on student achievement and are a benchmark for an educator. The factors that influence student achievement include external and internal factors. Internal factors include physical and spiritual health, as well as student psychology. while external factors include family, school and community.